2017
DOI: 10.3389/fendo.2017.00317
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis on Single Small Yellow Follicles Reveals That Wnt4 Is Involved in Chicken Follicle Selection

Abstract: Ovarian follicle selection is an important process impacting the laying performance and fecundity of hens, and is regulated by follicle-stimulating hormone (FSH) through binding to its receptor [follicle-stimulating hormone receptor (FSHR)]. In laying hens, the small yellow follicle (6–8 mm in diameter) with the highest expression of FSHR will be recruited into the preovulatory hierarchy during ovarian follicle development. The study of molecular mechanism of chicken follicle selection is helpful for the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…expression is helpful for elucidating mechanisms underlying follicle selection in chicken. By previous study we uncovered the role of Wnt4 in chicken follicle selection [4]. In this study, for the first time, we performed an integrated transcriptomic analysis on these SY follicles, identified an interaction network of SOWAHA, Integrated analysis indicated that the expression of SOWAHA was regulated by three miRNAs, i.e.…”
Section: Systemic Transcriptomic Analysis On Expression Differences Bmentioning
confidence: 85%
“…expression is helpful for elucidating mechanisms underlying follicle selection in chicken. By previous study we uncovered the role of Wnt4 in chicken follicle selection [4]. In this study, for the first time, we performed an integrated transcriptomic analysis on these SY follicles, identified an interaction network of SOWAHA, Integrated analysis indicated that the expression of SOWAHA was regulated by three miRNAs, i.e.…”
Section: Systemic Transcriptomic Analysis On Expression Differences Bmentioning
confidence: 85%
“…The dynamic and highly regulated process requires the coordinated actions of a great number of genes, which is orderly orchestrated at the transcriptional and post-transcriptional levels [2]. While some of genes like Wnt family member 4 (Wnt4) [3], parathyroid hormone like hormone (PTHLH) [4], cytochrome P450 family 11 subfamily A member 1 (CYP11A1) [5] have been known are related to follicle development, new regulators continue to be uncovered. With the discovery of small RNAs that exert additional layers of control on gene expression, studies have begun looking at the roles these molecules play regulating cellular events in the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, this process seems to be complex and highly coordinated, involving a number of divergent biological effects on the maturation of oocytes and differentiation and proliferation of granulosa and theca cells within the ovarian follicles [8]. In addition, the follicle-stimulating hormone (FSH) has been implicated in facilitating the recruitment of follicles [6,7,[9][10][11][12]. Similarly, follicle stimulating hormone receptors (FSHR) are reportedly expressed on the granulosa layer of developing follicles, and mRNA expression of these receptors (FSHR) changes with progressing follicular maturation [3,6,13].…”
Section: Introductionmentioning
confidence: 99%